2023
DOI: 10.1039/d3lc00062a
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic in-line dynamic light scattering with a commercial fibre optic system

Abstract: We report the coupling of dynamic light scattering (DLS) in microfluidics, using a contact-free fibre-optic system, enabling the under-flow characterisation of a range of solutions, dispersions, and structured fluids. The...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…These data show, perhaps, more clearly how the maximum for this physicochemical property shifts toward the equimolar ratio with increasing concentration. This increase in apparent translational diffusion coefficient has been observed and explained previously as DLS measures the mutual diffusion coefficient of micelles, monomers, and counterions in solution. For uncharged micelles in solution, such as those formed by DDAO in neutral to basic conditions, the mutual diffusion coefficient equals the micellar diffusion as can be seen at all concentrations investigated from Figure b at 100% DDAO, where the near constant micelle radii from SANS for DDAO micelles with concentration are supported by little to no change in diffusion coefficient. However, for SDS micelles, which increase in polar radius from 16 Å at 10 mM to 25 Å at 50 mM, we observed an increase in apparent diffusion coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…These data show, perhaps, more clearly how the maximum for this physicochemical property shifts toward the equimolar ratio with increasing concentration. This increase in apparent translational diffusion coefficient has been observed and explained previously as DLS measures the mutual diffusion coefficient of micelles, monomers, and counterions in solution. For uncharged micelles in solution, such as those formed by DDAO in neutral to basic conditions, the mutual diffusion coefficient equals the micellar diffusion as can be seen at all concentrations investigated from Figure b at 100% DDAO, where the near constant micelle radii from SANS for DDAO micelles with concentration are supported by little to no change in diffusion coefficient. However, for SDS micelles, which increase in polar radius from 16 Å at 10 mM to 25 Å at 50 mM, we observed an increase in apparent diffusion coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…The system was capable of carrying out composition mapping measurements under flow with dynamically varying compositions, with integration times ranging from approximately 3 to 10 s. It was found that a glass capillary-connected device featuring a 1 mm internal diameter has certain advantages in terms of experimental robustness and ease of operation. Reducing the channel dimensions increases the shear gradients and requires high precision in optical alignment, and issues such as parasitic light refraction and reflections from the channel walls become more prominent [ 205 ].…”
Section: Scattering-based Detection Techniquesmentioning
confidence: 99%
“…Light Scattering [198,199,[201][202][203][204][205] • In the future, the integration of AI into these devices heralds a transformative change in signal processing, improving sensitivity and real-time analysis through machine learning. The automation of experimental optimization by AI will streamline processes and facilitate signal processing, guaranteeing the efficiency and reproducibility of measurements and experiments.…”
Section: Dynamicmentioning
confidence: 99%
“…Furthermore, it has been shown that the in-line integration of DLS equipment in the manufacturing process allows particle size distributions to be measured during the process. 14 However, due to its measurement principle, DLS is strongly influenced by large particles, making it difficult to obtain accurate particle size distributions for samples containing impurities such as agglomerates. In recent years, this challenge has been addressed by the nanoparticle tracking analysis (NTA), which measures particle size distributions by calculating the diffusion coefficient via tracking the movement of a single nanoparticle using optical video images and has attracted attention as a new analytical method to replace the conventional DLS method.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Dynamic light scattering (DLS) measurements are commonly used to assess the particle size distribution of liposomes. Furthermore, it has been shown that the in-line integration of DLS equipment in the manufacturing process allows particle size distributions to be measured during the process . However, due to its measurement principle, DLS is strongly influenced by large particles, making it difficult to obtain accurate particle size distributions for samples containing impurities such as agglomerates.…”
Section: Introductionmentioning
confidence: 99%